(untitled) - Allison, Lizabeth Ann (New York, 2007)
More accessible to beginning students in the field than its encyclopedic counterparts, Fundamental Molecular Biology provides a distillation of the essential concepts of molecular biology, and is supported by current examples, experimental evidence, an outstanding art program, multimedia support and a solid pedagogical framework
Keywords: Sinh học phân tử,Nucleic acids.,Molecular biology.,Sinh học phân tử